Design Based the δ Operator of the Minimum Beat System - Zhou Shiqun; Wang Ping (Institute of Advanced Engineering and Science, 2013)
Digital controller simulation using MATLAB the minimum beat deviation system z domain, and transformed it in δ domain. Using the δ transformation’s nature of approximating the continuous domain in small sampling period, we simulated the controller. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1894